If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8z + 1 + -1z = 6 + 6z + 6 Reorder the terms: 1 + 8z + -1z = 6 + 6z + 6 Combine like terms: 8z + -1z = 7z 1 + 7z = 6 + 6z + 6 Reorder the terms: 1 + 7z = 6 + 6 + 6z Combine like terms: 6 + 6 = 12 1 + 7z = 12 + 6z Solving 1 + 7z = 12 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 1 + 7z + -6z = 12 + 6z + -6z Combine like terms: 7z + -6z = 1z 1 + 1z = 12 + 6z + -6z Combine like terms: 6z + -6z = 0 1 + 1z = 12 + 0 1 + 1z = 12 Add '-1' to each side of the equation. 1 + -1 + 1z = 12 + -1 Combine like terms: 1 + -1 = 0 0 + 1z = 12 + -1 1z = 12 + -1 Combine like terms: 12 + -1 = 11 1z = 11 Divide each side by '1'. z = 11 Simplifying z = 11
| 4*x=x | | Y=x^3+c^2-12x | | hbt=2(3.14) | | 0.75x=92 | | 3y=19x+86 | | (3y^3/4a^5y)*(10a^3/y) | | (n+6)(n-6)=5n | | 7+6x=5+3x | | -6=-5x+x^2 | | 11(v+4)-3v=4(2v+3)-17 | | 27d^6+8g^12=0 | | 3+2w=19 | | (x)=-2x^2+7x-4 | | 2lnx+4=5+lnx | | wx^2-w^2x^2=0 | | F(x)=5x^2+10x+12 | | 6t+8=26-3t | | 6y-1=8y-3y | | x/2=3-x/4 | | 8x^3-12x^2-10x+15= | | (x-1)/7-(x-3)/2=1 | | X=4x^2-9x+2 | | 4a+6=36 | | (x)=-2x^2+9x+5 | | x-.03x=158.92 | | 2g+6=6g-6 | | H(x)=-2x^2+9x+5 | | F(x)=4cos^2-6sin^2x | | x-3y=y+2x | | 4z-1=7z+4z | | (2x+16)=(4x-4) | | 3x^2+5=-3x+6 |